PERGUMULAN ADAT DAN AGAMA (NIKAH SASUSUKU DI MINANGKABAU DALAM NOVEL SALAH PILIH KARYA NOER SUTAN ISKANDAR) - Merry Kurnia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The paradoxical Minangkabau custom makes it a unique thing, the dualism of the power of syarak and adat seems to be able to go hand in hand as sounded in the traditional philosophy, adat basandi syarak, syarak basandi kitabullah. But in reality both are vulnerable to attacking each other because adat and syarak have different perspectives in many ways, these differences carve a history of painful civil war in the Minangkabau (Paderi Movement). The majority of the Minangkabau people view syarak and adat as possible, as if hypnotized by the traditional philosophy that is upheld, this article tries to reveal that the battle of adat and religion still occurs today. It is seen from the marriage case that the entries in the novel were wrongly chosen by Noer Sutan iskandar which was contrary to adat but not according to religion. The technique of collecting data is done by literature studies and interviews, the results are astounding. Criticisms with the theme of un-customary customs and religion have been going on for a long time, even many massive literary works have raised the theme, until now with different epochs of life. religion is never over.